Towards Self-evolving Context-aware Services - Autili, Marco; Di Benedetto, Paolo; Inverardi, Paola; Tamburri, Damien (Electronic Communications of the EASST, 2008)
The introduction of new communication infrastructures such as Beyond 3rd Generation (B3G) and the widespread usage of small computing devices are rapidly changing the way we use and interact with technology to perform everyday tasks. Ubiquitous networking empowered by B3G networking makes it possible for mobile users to access networked software services across continuously changing heterogeneous infrastructures by resource-constrained devices. Heterogeneity and devices’ limitedness, create serious problems for the development and dynamic deployment of mobile applications that are able to run properly on the execution context and consume services matching with the users’ expectations. Furthermore, the everchanging B3G environment calls for applications that self-evolve according to context changes. Out of these problems, self-evolving adaptable applications are increasingly emerging in the software community. In this paper we describe how CHAMELEON, a declarative framework for tailoring adaptable applications, is being used for tackling adaptation and self-evolution within the IST PLASTIC project.